2007
DOI: 10.1093/jmt/44.4.329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Background Stimulative Music on Behavior in Alzheimer's Patients

Abstract: Previous studies have demonstrated the benefits of music therapy in Alzheimer's patients, focusing either on improvement of healthy cognitive and social skills, or reduction of agitation symptoms. The present study examined the effect of background music on both positive and negative behaviors, during a time in which patients were not occupied with any structured activity. Twenty eight participants were observed both with and without stimulative, familiar background music. Results showed both a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 0 publications
1
30
0
2
Order By: Relevance
“…Several studies have linked music to a decrease in agitation and/or apathy in persons with dementia 3133 and an increase in positive social behaviors. 34 Gotell et al 35 found that music increased awareness of and interest in their environment in persons with dementia. Our results agree with those findings in that music produced significantly higher levels of interest and pleasure than the baseline condition ( P < .001 for both in paired-sample t tests; results are available from the authors).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked music to a decrease in agitation and/or apathy in persons with dementia 3133 and an increase in positive social behaviors. 34 Gotell et al 35 found that music increased awareness of and interest in their environment in persons with dementia. Our results agree with those findings in that music produced significantly higher levels of interest and pleasure than the baseline condition ( P < .001 for both in paired-sample t tests; results are available from the authors).…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, moderate effects of any form of music therapy may be effective in reducing dementia troubles. Thus, those studies have showed the benefits of music therapy in Alzheimer's patients, focusing either on the improvement of healthy cognition, such as autobiographical memory [2022], semantic memory [23], language ability [24], and cognitive function [21], or on neuropsychiatric symptoms, such as agitation [2527], apathy [28], depression, and anxiety [29]. Furthermore, several studies showed that the musical familiarity can elicit certain affective responses [20, 24, 3033], even also new musical stimuli could do it [34].…”
Section: Introductionmentioning
confidence: 99%
“…Since music therapy might be able to enhance aspects such as the affective state, behaviour, life experiences or a person's life history by providing access to lost memories of life events and people [20, 21, 24, 25]—which are considered aspects of SC—, we set out to determine whether familiar songs could enhance self-consciousness in patients with Alzheimer's disease. So, the purpose of our study was to examine the impact of familiar musical intervention versus nonfamiliar musical intervention on several aspects of SC in AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a significant increase in positive social behaviors as well as a decrease in negative behaviors (eg, agitation, aggression, wandering) when the music was played in the background. 100 Finally, Garland et al 101 compared the effects of exposure to 3 types of 15-minute audiotapes (comprising favorite music, simulated family presence, or text reading) to the usual care situation in 30 nursing home PWDs with frequent behavioral disturbances. All auditory stimuli, including music, were found to temporarily reduce the amount of physically and verbally agitated behaviors.…”
Section: Caregiver-implemented Musical Activities and Dementiamentioning
confidence: 99%